MEDICO-ECONOMIC SUBSTANTIATION OF NORMATIVE STANDARD OF SUPPLYING STUDENTS OF MILITARY SCHOOLS WITH MEDICATIONS - Yu. V. Miroshnichenko; V. S. Gaynov (IRBIS LLC, 2015)
the study presents a characteristic of new normative act prepared by the Russian Federation Ministry of Defense stating a normative standard of supplying an operative dentistry of military schools students with medications and materials. A practical use of the normative standard will allow increasing of efficiency of medical supply of students and improving their health state.